Analisis Profesionalisme Terhadap Kepemimpinan Dan Kesiapan Menghadapi Perubahan Organisasi: Suatu Tinjauan Literatur - Misbachul Munir (CV. Ulil Albab Corp, 2025)
Professionalism in leadership is a crucial aspect that influences organizational readiness to face change. In the current era of globalization and digitalization, changes in organizations occur rapidly and often unexpectedly. Professional leaders are expected to be able to lead organizations through transition periods effectively. Therefore, it is important to understand how professionalism in leadership can improve organizational readiness to face change. This study aims to analyze the relationship between professionalism in leadership and organizational readiness to face change through a comprehensive literature review. The main focus of this study is to evaluate the extent to which aspects of professionalism in leadership, such as competence, ethics, and responsibility, contribute to organizational adaptability and flexibility. The method used in this study is a systematic literature review. Searches were conducted on various academic databases to find articles, journals, and books that are relevant to the topic of professionalism in leadership and organizational readiness to face change. Inclusion criteria included publications that discussed related topics theoretically and empirically. The data obtained were analyzed qualitatively to identify key themes and gaps in previous research. Professional leaders tend to have good communication skills, the ability to make wise decisions, and sensitivity to market dynamics. In addition, ethical and responsible leadership creates an adaptive and innovative organizational culture. However, several studies also show that contextual factors such as organizational culture and hierarchical structure can affect the effectiveness of leadership professionalism. From this literature review, professionalism in leadership plays an important role in improving organizational readiness for change. The limitations of this study include limited accessibility to certain literature and potential bias in source selection. The findings that will be produced in this study will provide a strong foundation for further research on change management strategies in organizations.